The Impact of Social Media Use on Students' Concentration and Motivation to Learn in Elementary School - Azhar Muzaqy, Chaedar; M. Suud, Fitriah (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2025)
In today's modern era, the use of social media is one of the parts that cannot be separated, especially in elementary school students, where the use of social media has the potential to affect students' concentration and motivation to learn. With this study, the aim is to find out  the impact of the use of social media on the concentration and learning motivation of Muhammadiyah Sambisari elementary school students. The use of methods in this study is qualitative descriptive, in nature with a case study approach. Data were collected through in-depth interviews with eight fifth-grade students, homeroom teachers, and the principal, as well as direct observation of student learning behavior. Data analysis was conducted through data reduction, presentation, and conclusion drawing, validated through triangulation. The use of social media has a significant impact: 55% of students experience concentration problems (such as loss of focus and drowsiness due to interesting content), while 60% report a decrease in motivation to study (such as laziness and forgetting assignments). However, 45% of students are not distracted, and 40% use social media positively to search for learning materials (e.g., via YouTube). School efforts include banning gadgets at school, religious programs such as praying on time, memorizing the Qur'an, and praying Dhuha in congregation, as well as parenting for parents. The results confirm that the negative impact of social media is more dominant than the positive. The implication of this study is to reveal the importance of collaboration between schools and parents as a form of efforts to handle the use of social media in children, including using a religiosity approach such as the existence of timely prayer programs, tahfidz qur'an, and congregational dhuha prayers which are proof that a religious approach to students can strengthen students' character, but also improve their focus, concentration, and motivation to learn.